Association of interleukin 4 and MTHFR gene polymorphisms with distal symmetrical polyneuropathy in young diabetics - Silva, Raquel Garcia Rocco da; Lima, Marcelo A. Costa; Moura, Claudia de Melo; Luescher, Jorge Luiz; Campos, Ludmila Nascimento Rodrigues; Silva, Daniel de Souza e; Ribeiro, Márcia Gonçalves (Arquivos de neuro-psiquiatria, 2024)
Background It is believed that genetic factors play a role in the development and severity of neural injury among people with distal symmetrical polyneuropathy (DSP), because some genes are involved in specific biological pathways, acting in different ways in the pathogenic process. Objective To identify potential associations involving the 5,10-methylenetetrahydrofolate reductase (MTHFR C677T) and interleukin 4 (IL-4 intron 3 variable number of tandem repeats [I3VNTR]) gene polymorphisms and DSP in the studied sample. Methods In total, 70 children and adolescents with type-1 diabetes underwent a nerve conduction studie (NCS) of the sural nerve. Saliva samples were collected for DNA extraction and genotyping of the MTHFR C677T and IL-4 I3VNTR polymorphisms. Results The prevalence of DSP was 15.71%. The participants with DSP presented higher mean levels of glycated hemoglobin, triglycerides, total cholesterol, and low-density lipoprotein (LDL) (p > 0.05). The NCS amplitudes were lower in individuals with DSP (p = 0.00). The mean conduction velocity was lower in people with the A1A1 genotype (p = 0.02). Maternal and paternal history of diabetes in great-grandparents were associated with DSP (p = 0.04 and 0.02, respectively). Glycated hemoglobin and impaired Achilles reflex were associated with the MTHFR CC genotype (p = 0.04 and 0.05 respectively) and high-density lipoprotein (HDL) cholesterol was associated with the MTHFR CT genotype (p = 0.05). We found no association between the polymorphisms investigated and DSP. Conclusion In the present study, we found no association involving the MTHFR C677T and IL-4 I3VNTR polymorphisms and DSP. However, the study provides other associations and suggests possible implications for these findings.